PANDANGAN ISLAM TENTANG PENETAPAN UPAH MINIMUM REGIONAL (UMR) - Budi Solihin (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2018)
In the labor economy it is an active resource which is one of the smooth factors of production. In Islam, human beings were created to become caliphs who can preserve and utilize this earth well, so that every work done becomes a worship for these humans. But what happened in the modern era like now, especially in Indonesia, is known as the Regional Minimum Wage (UMR) stipulation for workers who are intended for justice in terms of wages, but the fact that there are still labor demonstrations during May Day that feel they have not been treated fairly by government in terms of stipulating wages. The purpose of this study is to analyze how the views of Islam in the determination of the UMR. The method in this study uses qualitative analysis with data collection techniques through literature studies and interviews with several workers. It turns out that in Islamic wage setting has been around since the days of classical economic thinkers, it's just that nowadays in the government UMR determination tends to be pro against employers, it is not easy to make a fair decision on both parties between workers and those who give work, but the facts that occur that's right. So that in Islam it is necessary to pay attention to justice and clear contract agreements between workers and employers so that no party feels deprived.